The Algerian War (1954-1962) Women in combat Danièle Djamila Amrane Minne: حَرْبُ الجزائر (1954-1962) نِســـــــــــاءٌ مُقــــاتِــلات دانييل جميلة عمران مــــــــين - BENDRIMIA , Salah Eddine (Maalim, 2026)
This article is a translation of the first part of the book by the late mujahida Danièle Djamila Amrane Minne, entitled: La guerre d'Algérie (1954-1962): Femmes au combat (The Algerian War (1954-1962): Women Fighters). Originally a doctoral thesis, the author collected testimonies from female fighters who participated in the war of liberation, particularly in the Battle of Algiers, in which she herself played an active role. She sought to highlight the role of women in liberating the country and restoring the dignity of the Algerian people, a role that was ignored by writers, fighters and officials after independence. She showed that Algerian women were not only a support for men, but also an indispensable and effective element in the liberation revolution.